Evaluasi Formulasi Sediaan Floating Mikroenkapsulasi yang Mengandung Ekstrak Etanol Herba Sirih Cina (Peperomia pellucida L.) - Cut Inssy Mulun; Razoki Razoki; Erida Novriani (Pusat riset dan Inovasi Nasional, 2025)
Background: Chinese betel (Peperomia pellucida L.) is an herbal plant rich in bioactive compounds such as flavonoids, alkaloids, and tannins that have the potential to be antioxidants, antimicrobials, and antidiabetics. However, the stability and absorption of its active compounds in the body is still a challenge. Microencapsulation technology and a floating drug delivery sistem (FDDS) can improve the effectiveness and stability of herbal preparations. Objective: This study aims to formulate and evaluate floating microencapsulation preparations containing Chinese betel herb ethanol extract using modern drug delivery technology. Methods: Ethanol extracts were obtained by maceration method and formulated by ionic gelation technique using a combination of sodium alginate and chitosan at three concentration variations (0.25%, 0.5%, and 0.75%). The evaluation included morphological analysis with SEM, ex vivo buoyancy test on the stomach of Wistar rats, determination of moisture content, and physical stability test using the cycling test method. Results: Microencapsulation with a concentration of 0.75% showed the most compact and delicate morphology, the lowest moisture content (0.64%), and the best physical stability. All formulations are capable of floating, with the longest buoyancy time at a concentration of 0.25% for 8 hours. There were no significant physical changes after six cycles of extreme temperatures. Conclusion: Microencapsulation preparations of Chinese betel ethanol extract in a natural polymer-based floating system show good stability and potential as an innovative herbal formulation to extend retention time in the stomach.